(untitled) (Stamford Journal of Microbiology, 2021)
Over past few years, people are giving more attention to air pollution and its effects on human health. Due to the high population density in Bangladesh, air pollution is a major issue in metropolitan areas, especially in Dhaka city. Present study aims to isolate air-borne microbes from the inside environment of public transport and different types of microbes that are frequently encountered by commuters when they touch the interior surfaces of vehicles used for public transport in Dhaka City. Atmospheric load of microorganisms was measured with petri dish which was kept open for 30 minutes in the sampling locations and swabs were taken from interior surfaces of vehicles. Air samples collected from both bus and railway stations showed a high atmospheric microbial count (total viable bacteria and total fungal count were 140 to 776 CFU/plate/30 min and 27 to 168 CFU/plate/30 min, respectively). A similar outcome was found after analysis of swab samples of the contact surfaces of the vehicles as well. A total of four bacterial pathogens were identified from the interior surfaces of the vehicle including Escherichia coli, Bacillus spp., Pseudomonas spp. and Vibrio spp. which are known to be associated with gastrointestinal tract infection. To manage and control the environmental health risks caused by air pathogens, an authorized governmental agency should do continuous monitoring of air quality to reduce the negative effects and impacts of air pathogens on human and animal health. This research has shown a great concern to health practitioners in developing countries because these are pathogens that are mostly resistant to the commonly available antibiotics used in the treatment of infection associated with these pathogens. Most importantly, we need to raise awareness among the public in order to reduce the load and spread of pathogenic bacteria in the environment. Stamford Journal of Microbiology, Vol.11 (1) 2021: 7-10